Relationality and Learning in Oceania Contextualizing Education for Development - Johansson-Fua, Seu'ula; Jesson, Rebecca; Spratt, Rebecca; Coxon, Eve (Comparative and International Education: Diversity of Voices, 2020)
Relationality and Learning in Oceania: Contextualizing Education for Development critically engages debates in comparative education and international development relating to context, culture, language and indigenous epistemologies. It draws on experiences of a south-north research-practice team in Solomon Islands and Tonga.; Readership: All interested in comparative education and international development relating to context, culture, language and indigenous epistemologies. It draws on experiences of a south-north research-practice team in Solomon Islands and Tonga.